The effect of clinoptilolite on 137 Cs binding in broiler chickens - Vitorovic, Gordana; Slavata, Bratislava; Stosic, Katarina; Mladenovic, Verica; Vitorovic, Dusko (MTT Agrifood Research Finland, 2002)
The objective of this study was to evaluate the 137 Cs binding capacity of clinoptilolite.In the first in vitro experiment we investigated sorption of 137 Cs to natural and modified forms of clinoptilolite in highly acid solution,prepared to be similar to that of the gut of pigs (pH =2 3)at 37 ºC.In the second in vivo experiment 137 Cs binding to a modified form of clinoptilolite was studied in orally contaminated broiler chickens.137 Cs sorption in the high acidity solution depended on clinoptilolite concentration and varied between 30 85 %of the init ial activity.In the chickens,three hours after 137 Cs administration,there was 67%and 63%lower accumulation of 137 Cs in meat and edible organs (respectively)and seven hours after 137 Cs administration,there was 69% and 49% lower accumulation of 137 Cs in meat and edible organs (respectively)compared to the controls with no clinoptilolite added in food. Natural and modified forms of clinoptilolite have been shown to high sorption efficiency towards 137 Cs ions and could be recommended as possible radiocaesium binders in domestic animals.
Keywords: Ko; broilerit; siipikarja; cesium; clinoptilolite; 137 Cs; sorption; broilers